2015
DOI: 10.4238/2015.july.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fidelity and variability of micropropagated cassava plants (Manihot esculenta Crantz) evaluated using ISSR markers

Abstract: ABSTRACT. Molecular markers are efficient for assessing the genetic fidelity of various species of plants after in vitro culture. In this study, we evaluated the genetic fidelity and variability of micropropagated cassava plants (Manihot esculenta Crantz) using inter-simple sequence repeat markers. Twenty-two cassava accessions from the Embrapa Cassava & Fruits Germplasm Bank were used. For each accession, DNA was extracted from a plant maintained in the field and from 3 plants grown in vitro. For DNA amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…This demonstrates the existence of genetic variability between the genotypes evaluated. Similar results were found by Vidal et al (2015), who found a total polymorphism of 57.1%, when evaluating 22 M. esculenta accessions from the Germplasm Bank of Embrapa Cassava and Fruit Farming of Cruz das Almas, BA, Brazil. Silva et al (2011), however, found greater polymorphism (89.7%) in their evaluation of cassava genotypes of different origins (Indonesia, Brazil, and Thailand).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This demonstrates the existence of genetic variability between the genotypes evaluated. Similar results were found by Vidal et al (2015), who found a total polymorphism of 57.1%, when evaluating 22 M. esculenta accessions from the Germplasm Bank of Embrapa Cassava and Fruit Farming of Cruz das Almas, BA, Brazil. Silva et al (2011), however, found greater polymorphism (89.7%) in their evaluation of cassava genotypes of different origins (Indonesia, Brazil, and Thailand).…”
Section: Resultssupporting
confidence: 86%
“…ISSRs have proven to be an effective tool in the differentiation of species and varieties of the genus Manihot (Silva et al, 2011;Zayed et al, 2013;Vidal et al, 2015). The present study was conducted to evaluate the genetic diversity of cassava landraces grown by farmers in Alta Floresta, MT, Brazil, using ISSR molecular markers, with the aim to select material to compose a future germplasm bank of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on markers have been reported for several species, such as Ricinus communis L., Manihot esculenta (Vidal et al, 2015), Hevea brasiliensis (Mantello et al, 2012), and J. curcas (Cammellia et al, 2012). In these studies, the minimum number of locus markers was determined, which results in good accuracy and optimizes time and resources for genetic characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Ukpe and Mustapha (2016) reported that the increase in cassava yield is limited by several factors, among them the scarcity of planting material. Therefore, it is essential to develop techniques that increase the multiplication rate associated with high phytosanitary quality (Vidal et al, 2015). In vitro micropropagation is a technique for producing planting material with high phytosanitary quality on a large scale in a short period (Aladele and Kuta, 2008), but the high cost of this technique is its main disadvantage (Ogero et al, 2010).…”
Section: Introductionmentioning
confidence: 99%